2022
DOI: 10.1371/journal.pmed.1003955
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive factors and the risk of incident dementia: A cohort study of UK Biobank participants

Abstract: Background Women’s reproductive factors have been associated with the risk of dementia; however, these findings remain uncertain. This study aimed to examine the risk of incident all-cause dementia associated with reproductive factors in women and the number of children in both sexes and whether the associations vary by age, socioeconomic status (SES), smoking status, and body mass index (BMI) in the UK Biobank. Methods and findings A total of 273,240 women and 228,957 men without prevalent dementia from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 49 publications
8
47
0
1
Order By: Relevance
“…However, the definition of surgical menopause varied across studies, rendering firm conclusions difficult. In general, our findings for reproductive years align with another study using data from UK Biobank, showing that a shorter reproductive span, younger age at menopause and a history of hysterectomy were associated with greater risk for all-cause dementia 52 . Similarly, a shorter reproductive span with early age at natural or surgical menopause has also been linked to a higher risk of incident cardiovascular disease 53 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the definition of surgical menopause varied across studies, rendering firm conclusions difficult. In general, our findings for reproductive years align with another study using data from UK Biobank, showing that a shorter reproductive span, younger age at menopause and a history of hysterectomy were associated with greater risk for all-cause dementia 52 . Similarly, a shorter reproductive span with early age at natural or surgical menopause has also been linked to a higher risk of incident cardiovascular disease 53 .…”
Section: Discussionsupporting
confidence: 89%
“…The positive effects of parity on visual memory and simple processing speed corroborate previous results 19,20 . While a number of studies suggest a non-linear effect of number of childbirths on cognition 5,21 and all-cause dementia 52 , other studies did not replicate these associations 19 . Further studies are needed to confirm if any positive effect of parity on late-life cognition may be less pronounced in single-and grand-parous individuals.…”
Section: Discussionmentioning
confidence: 96%
“…This aligns with previous studies showing beneficial effects of a longer reproductive span on a number of brain health markers (Georgakis et al, 2016;Schelbaum et al, 2021;Subramaniapillai et al, 2022;Zeydan et al, 2019) and dementia risk (Gong et al, 2022). In line with previous studies (Day et al, 2015(Day et al, , 2017Zhao et al, 2021) we found an association between polygenic and phenotypic variance in reproductive span, but we found no associations between PGS and the brain measures, nor did PGS alter the interactions when included as a covariate.…”
Section: Discussionsupporting
confidence: 92%
“…Studies indicate that levels of cumulative oestrogen exposure, often assessed by reproductive span (age at menarche to age at menopause; (Fu et al, 2022;Gilsanz et al, 2019;Jett et al, 2022)), have lasting effects on brain structure and body composition even after menopause. For example, a longer reproductive span has been linked to larger GM volumes (Schelbaum et al, 2021), lower WM brain age (Subramaniapillai et al, 2022), and lower dementia risk in older-age samples (Fox et al, 2013;Gilsanz et al, 2019;Gong et al, 2022), although contrasting results have linked a longer reproductive span to increased risk of Alzheimer's disease (AD) (Najar et al, 2020;Geerlings et al, 2001). Age at menarche and menopause are also known to have genetic components (Fernández-Rhodes et al, 2018;Wang et al, 2019;Ruth et al, 2021), but the understanding of how the genetics underlying reproductive span relate to body composition and brain structure is limited (Roa-Díaz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The discourse of state costs and economic benefits in describing the value of hysterectomy has not considered long-term patient well-being or individual needs and interests (Fisher 1986). Nonetheless, a growing body of evidence suggests that there are important risk factors for diseases of ageing such as dementia and stroke, which are elevated by premenopausal hysterectomy (even with ovarian conservation) and which both increase aged-care costs to the state and are an important question for older patient well-being (Gong et al 2022;Shuster et al 2010;Bove et al 2014). Gynaecological surgeons practising premenopausal hysterectomy between 1870 and 2000 could not have been expected to take account of such long-term side effects which were only known to medical research from the early 2000s.…”
Section: Hysterectomy's Entanglements With Sterilisationmentioning
confidence: 99%